Mobility under the COVID-19 Pandemic: Asymmetric Effects across Gender and Age - Francesca Caselli; Francesco Grigoli; Damiano Sandri; Antonio Spilimbergo (Global Labor Organization (GLO), 2021)
Overall mobility declined during the COVID-19 pandemic because of government lockdowns and voluntary social distancing. Yet, aggregate data mask important heterogeneous effects across segments of the population. Using unique mobility indicators based on anonymized and aggregate data provided by Vodafone for Italy, Portugal, and Spain, we find that lockdowns had a larger impact on the mobility of women and younger cohorts. Younger people also experienced a sharper drop in mobility in response to rising COVID-19 infections. Our findings, which are consistent across estimation methods and robust to a variety of tests, warn about a possible widening of gender and inter-generational inequality.
Keywords: E1; I1; H0; 330; COVID-19; lockdown; mobility; gender; age